1999
DOI: 10.1152/ajpregu.1999.276.6.r1668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow and rapid cooling on catecholamine concentration in arterial plasma and the skin

Abstract: Norepinephrine (NE) and epinephrine (Epi) concentrations in arterial plasma and in skin tissue were measured chromatographically before and after external cooling. Urethan-anesthetized rats were cooled either slowly (0.004–0.006°C/s) or rapidly (0.03– 0.05°C/s). Blood samples were drawn three times from each animal: 1) before cooling and at a rectal temperature decreased 2) by 0.5°C and 3) by 3–4°C. Skin samples were taken from controls and from rapidly or slowly cooled rats at a rectal temperature lowered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The measurements of Kozyreva et al (1999) showed that both adrenaline and noradrenaline exist in rat skin. Also, earlier research identified chromaffine cells in the cat skin (Burch and Phillips 1958).…”
Section: Discussionmentioning
confidence: 97%
“…The measurements of Kozyreva et al (1999) showed that both adrenaline and noradrenaline exist in rat skin. Also, earlier research identified chromaffine cells in the cat skin (Burch and Phillips 1958).…”
Section: Discussionmentioning
confidence: 97%
“…after nonepinephrine treatment and vasoconstriction, although at low vascular tone) [9]. Probably, potentiation of vasoconstriction during SC in rats receiving SP and the absence of the modulatory effect of this peptide on vascular reactions induced by RC can be explained by differences in the degree of sympathetic activation during various cooling rates [5].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that dynamic activity of peripheral thermoreceptors plays an important role in the regulation of functional systems, maintaining temperature homeostasis and in modulation of the hormonal status of the organism during cooling. It can be hypothesized that different degree of participation of sympathetic system during various modes of cooling [3][4][5] can be one of the reasons underlying different effects of SP observed during RC and SC.…”
Section: Resultsmentioning
confidence: 99%
“…17 On the one hand, rapid skin cooling evokes a significant increase in plasma catecholamines with a reduction in skin catecholamines. The fall in skin catecholamines is attributed to their local release to cause vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%